Optimization of Passing Skills Using the Inside of the Foot in Football Games for Students of MTs Nurul Ulum, Malang Regency - Putra, Bagas Adi; Mushofi, Yuskhil; Junaidi, Ahmad; Setyawan, Trinovandhi; Pawitra, Paulus Rah Adi; Windriyani, Shinta Masitho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Based on the results of observations at MTSS Nurul Ulum, Malang Regency, researchers still found several students who did not understand the skills of several passing techniques in soccer games, especially in passing techniques using the inside of the foot, so that the game seemed haphazard. This was possibly caused by the students' inability to master passing using the inside of the foot. This study used the classroom action research (CAR) method. Generally speaking, in classroom action research, there are four stages that are commonly passed, namely, (1) planning, (2) action, (3) observation, (4) reflection. From the results of the study, it can be concluded that there is an increase in passing skills using the inside of the foot in students at MTSS Nurul Ulum, Malang Regency.